2019
DOI: 10.1039/c9ra01623f
|View full text |Cite|
|
Sign up to set email alerts
|

Structural characterization and anti-inflammatory potency of Mesobuthus martensii Karsch oligopeptides in lipopolysaccharide (LPS)-induced RAW264.7 macrophages

Abstract: Scorpion venom represents a significant source of bio-active peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Peptide HYGH showed different mechanisms of action by regulation of NF-κB together with MAPK inflammatory signaling pathways along with suppressing NO production by 76.8%. 64 Anti-inflamamtory peptide GKLTKDKLKRGAKKALNVASKV (Sibasec) has also been extracted from the salivary glands of black fly ( Simulium bannaense ) after determining its amino acid composition by cDNA sequencing. 105 Since flies attract attention due to their good nutritional value (17.5–67 g per 100 g protein), more peptides with anti-inflammatory potential such as Cecropin-TY1 were discovered from salivary glands of horsefly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptide HYGH showed different mechanisms of action by regulation of NF-κB together with MAPK inflammatory signaling pathways along with suppressing NO production by 76.8%. 64 Anti-inflamamtory peptide GKLTKDKLKRGAKKALNVASKV (Sibasec) has also been extracted from the salivary glands of black fly ( Simulium bannaense ) after determining its amino acid composition by cDNA sequencing. 105 Since flies attract attention due to their good nutritional value (17.5–67 g per 100 g protein), more peptides with anti-inflammatory potential such as Cecropin-TY1 were discovered from salivary glands of horsefly.…”
Section: Resultsmentioning
confidence: 99%
“…25,60 Finally, the bioactivity of purified peptides is validated in vitro and/or in vivo through the quantification of inflammatory mediators such as prostaglandin E2 (PGE2), TNF-α, IL-6, IL-1β, IL-10, IL-8, VCAM-1 or NO in cell lines or by measuring the inhibition of enzymes involved in inflammation such as COX-2, LOX and iNOS. [61][62][63][64] Nonetheless, current techniques for separation, purification, identification, and quantification of biopeptides from their natural matrices are limited by high technicality and high cost, which restricts their therapeutic competitiveness and industrial application. 53 Processes for peptide preparation and identification represent an analytical challenge because they implie high yield and purity for the quantification of its potential bioactivity and the validation of their structure-activity relationship.…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, CMO-1 inhibited the degradation of IkBα and the nuclear translocation of p65. It also suppressed NF-kβ activation and inhibited MAPK phosphorylation of ERK, JNK, and p38 [ 116 ]. The venom of another species of Mesobuthus ( Mesobuthus eupeus - lesser Asian scorpion , the lesser Asian scorpion, or the mottled scorpion) was effective in treating CFA-induced arthritis, in which the edema reduction correlated with the reduction of arthritis [ 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…The relative expression ratios of phospho-p38 and p38 MAPK were lower in M-YPLP and H-YPLP groups than in the NC group (p < 0.05), suggesting YPLP could inhibit the phosphorylation of p38 MAPK. Zheng et al 49 observed that (scorpion venom) oligopeptides reduced inflammation levels and inhibited the expression of phospho-p38. We speculated that YPLP improved muscle physiological processes via the p38 MAPK signal pathway.…”
Section: Analysis Of Daps Between H-yplp and Nc Groups The Informatio...mentioning
confidence: 99%